PENGARUH STRES KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN OUTSOURCING PADA PT. BANK JATENG CABANG KOORDINATOR DAN CABANG PEMBANTU WILAYAH KOTA SEMARANG - Yoanisa Mahardiani; Ari Pradhanawati (Universitas Diponegoro, 2013)
The research is motivated by the fact that many companies today use outsourced labor. One of them is PT. Bank Jateng Semarang. The number of employes’ absence from work, due to illness or other reasons, increases from 2010 to 2011 which indicates the pressence of stress at work and a problem with the physical work environment which in turn will have an impact on employees performance. The purpose of this study is to determine the effect of work stress and physical work environment to the performance of outsorcing employees at PT. Bank Jateng Semarang. In this explanatory ​​research, data are collected using questionnaires. The method of analysis used in this study is linear regression. The analysis shows that job stress has no significant effect to the employee's performance. The company is expected to pay more attention to the outsourced employees, so they can improve the performance of the company.